2005
DOI: 10.1080/09540120412331336661
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge and acceptability of HAART among TB patients in Durban, South Africa

Abstract: From October 2002 to February 2003, we conducted semi-structured interviews on knowledge of HIV, antiretroviral treatment, and willingness to participate in voluntary counselling and testing and HAART with 54 consenting patients attending a tuberculosis (TB) clinic in Durban, South Africa. 74% of patients interviewed reported not knowing anything about antiretroviral treatment (HAART). Knowledge of antiretroviral drugs (ARVs) was restricted to use in preventing mother to child HIV transmission (MTCT). 57.4% of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2007
2007
2010
2010

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 11 publications
(8 reference statements)
1
11
0
Order By: Relevance
“…In this comparison, having sufficient ART knowledge was defined as having a score of 50% and higher in Kabarole sample. Another study in tuberculosis patients from South Africa revealed a much lower (Gebrekristos et al, 2005). This comparison is naturally limited, taking into account that different score assessment tools were used, but nevertheless gives a magnitude of the difference in the scores.…”
Section: Discussionmentioning
confidence: 91%
“…In this comparison, having sufficient ART knowledge was defined as having a score of 50% and higher in Kabarole sample. Another study in tuberculosis patients from South Africa revealed a much lower (Gebrekristos et al, 2005). This comparison is naturally limited, taking into account that different score assessment tools were used, but nevertheless gives a magnitude of the difference in the scores.…”
Section: Discussionmentioning
confidence: 91%
“…A WHO report on the global access to anti-retroviral therapy [55] speculated that the relative over-representation of women in ART programmes could be because women are better integrated into community networks, and thus have better health-care information and are better able to access public health facilities than are men, especially where these women access PMTCT programmes. Closely related, recent studies suggest that antenatal clinics are often the first point of entry into HIV/AIDS prevention, care and treatment [56,57]. Nattrass (2008) hypothesised that South African men with AIDS-related illnesses are less likely to access ART than their female counterparts because masculine norms encourage them to deny weakness and to avoid seeking treatment for any ailment for as long as possible [54].…”
Section: Discussionmentioning
confidence: 99%
“…Yet, as few as 5 Á57.4% of TB patients get tested for HIV. It is estimated that fewer than 10% are aware of their current serostatus (Gebrekristos et al, 2005;Grimwade et al, 2005;WHO, 2002b;WHO/UNAIDS, 2003).…”
Section: Settingmentioning
confidence: 98%